Integrated reporting and firm value: moderating role of CEO integrity in the context of GCC countries - Mohammed Saleem Alatawi; Zaidi Mat Daud; Jalila Johari (Cogent Business & Management)
The study examines the impact of Integrated Reporting (IR) on firm value, and it explores the moderating role of CEO integrity (CEOI) in this relationship for companies listed on GCC stock exchanges. The sample consists of 177 listed firms from six GCC countries (Saudi Arabia, UAE, Bahrain, Qatar, Oman, and Kuwait) that published integrated reports from 2017–18 to 2022–23 in Arabic and English. Using secondary data from the firms’ websites, the research applies the system GMM model and dynamic fixed-effect robust standard error model to analyze the data. The findings reveal that IR positively influences firm value. Furthermore, CEO integrity moderates the relationship between IR and firm value, amplifying the positive effects of IR when CEOs demonstrate ethical leadership. The study’s implications suggest that firms should adopt IR practices and ensure CEO integrity to boost firm value. Supervisory boards must oversee both IR practices and CEO performance to maintain transparency, safeguard the firm’s reputation, and drive sustainable value creation.